Antiepileptic Effects of Protein-Rich Extract from Bombyx batryticatus on Mice and Its Protective Effects against H2O2-Induced Oxidative Damage in PC12 Cells via Regulating PI3K/Akt Signaling Pathways. (6th May 2019) - Hu, Meibian; Liu, Yujie; He, Liying; Yuan, Xing; Peng, Wei; Wu, Chunjie
Abstract : Bombyx batryticatus is a known traditional Chinese medicine (TCM) utilized to treat convulsions, epilepsy, cough, asthma, headaches, and purpura in China for thousands of years. This study is aimed at investigating the antiepileptic effects of protein-rich extracts from Bombyx batryticatus (BBPs) on seizure in mice and exploring the protective effects of BBPs against H2 O2 -induced oxidative stress in PC12 cells and their underlying mechanisms. Maximal electroshock-induced seizure (MES) and pentylenetetrazole- (PTZ-) induced seizure in mice and the histological analysis were carried out to evaluate the antiepileptic effects of BBPs. The cell viability of PC12 cells stimulated by H2 O2 was determined by MTT assay. The apoptosis and ROS levels of H2 O2 -stimulated PC12 cells were determined by flow cytometry analysis. Furthermore, the levels of malondialdehyde (MDA), superoxide dismutase (SOD), lactate dehydrogenase (LDH), and glutathione (GSH) in PC12 cells were assayed by ELISA and expressions of caspase-3, caspase-9, Bax, Bcl-2, PI3K, Akt, and p-Akt were evaluated by Western blotting and quantitative real-time polymerase chain reaction (RT-qPCR) assays. The results revealed that BBPs exerted significant antiepileptic effects on mice. In addition, BBPs increased the cell viability of H2 O2 -stimulated PC12 cells and reduced apoptotic cells and ROS levels in H2 O2 -stimulated PC12 cells. By BBPs treatments, the levels of MDA and LDH were reduced and the levels of SOD and GSH-Px were increased in H2 O2 -stimulated PC12 cells. Moreover, BBPs upregulated the expressions of PI3K, Akt, p-Akt, and Bcl-2, whereas they downregulated the expressions of caspase-9, caspase-3, and Bax in H2 O2 -stimulated PC12 cells. These findings suggested that BBPs possessed potential antiepileptic effects on MES and PTZ-induced seizure in mice and protective effects on H2 O2 -induced oxidative stress in PC12 cells by exerting antioxidative and antiapoptotic effects via PI3K/Akt signaling pathways.